Journey from Cultural Assimilation to Acculturation: Negotiating Identity in Gene Luen Yang’s American Born Chinese (SCHOLARS: Journal of Arts & Humanities, 2026)
This article scrutinizes the enduring nature of Orientalist stereotypes, identity, the assimilation pressures experienced by Asian Americans, and the internalization of racist accounts in Gene Luen Yang’s American Born Chinese. It contends that Yang exemplifies how stereotypes restrain subjectivity and falsify the pursuit of genuine belonging in the interrelated storylines of Jin Wang, the Monkey King, and Chin-Kee. For this purpose, this article employs the standpoints of the scholars Cheryl Harris, Richard Delgado, Jean Stefancic, and Derrick Bell’s Critical Race Theory (CRT) to critique racial power dynamics in the novel. Harris's perspective of ‘whiteness as property,’ Delgado and Stefancic's notion of ‘counter-storytelling,’ and Bell's viewpoint of the persistence of racism epitomize Yang's critique of systemic racism and the cultural irreconcilability existed in the American society. This article concludes that the racial hierarchies prevalent in American society dehumanize Asian American identities and emphasizes the necessity of recuperating cultural identity as a means of resistance and self-affirmation.  It expects to encourage scholars to study young adult fiction as a way to address racial inequality, redefine belonging, and challenge the biases that propagate injustice globally.